2022
DOI: 10.3389/fmicb.2022.1011102
|View full text |Cite|
|
Sign up to set email alerts
|

New perspectives on an old grouping: The genomic and phenotypic variability of Oxalobacter formigenes and the implications for calcium oxalate stone prevention

Abstract: Oxalobacter formigenes is a unique bacterium with the ability to metabolize oxalate as a primary carbon source. Most kidney stones in humans are composed of calcium and oxalate. Therefore, supplementation with an oxalate-degrading bacterium may reduce stone burden in patients suffering from recurrent calcium oxalate-based urolithiasis. Strains of O. formigenes are divided into two groups: group I and group II. However, the differences between strains from each group remain unclear and elucidating these distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In contrast to Eubacterium fissicatena, Oxalobacter, first reported as a novel anaerobic bacterium for degrading oxalic acids in 1985, is a popular species of interest to researchers in our literature search (55). Since the separation of Oxalobacter, numerous studies have concentrated on its role in hyperoxaluria and kidney stone development and attempted to develop associated therapies to limit the formation and advancement of the abovementioned diseases, owing to its specific function in degrading oxalic acid (56)(57)(58)(59). OxlT, an oxalate transporter protein of Oxalobacter, specifically absorbs oxalate from the intestine into bacterial cells, lowering the likelihood that the host animal may develop oxalate-deposition illnesses such as kidney stones (60).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Eubacterium fissicatena, Oxalobacter, first reported as a novel anaerobic bacterium for degrading oxalic acids in 1985, is a popular species of interest to researchers in our literature search (55). Since the separation of Oxalobacter, numerous studies have concentrated on its role in hyperoxaluria and kidney stone development and attempted to develop associated therapies to limit the formation and advancement of the abovementioned diseases, owing to its specific function in degrading oxalic acid (56)(57)(58)(59). OxlT, an oxalate transporter protein of Oxalobacter, specifically absorbs oxalate from the intestine into bacterial cells, lowering the likelihood that the host animal may develop oxalate-deposition illnesses such as kidney stones (60).…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was subcultured (1:50) into a colonic medium to assess toxin clearance in an environment more like the human gut than traditional bacteriological media. The colonic medium was prepared as previously described [56,57]. Briefly, the culture medium was prepared in ddH 2 O and consisted of (litre −1 ): 5 g starch, 5 g peptone water, 5 g tryptone, 4.5 g yeast extract, 4.5 g NaCl, 4.5 g KCl, 4 g mucin (porcine gastric type III), 3 g casein, 2 g pectin (citrus), 2 g xylan (oatspelt), 2 g arabinogalactan (larch wood), 1.5 g NaHCO 3 , 1.25 g MgSO 4 •7H 2 O, 1 g guar gum, 1 g inulin, 0.8 g cysteine, 0.5 g KH 2 PO 4 , 0.5 g K 2 HPO 4 , 0.4 g bile salts No.…”
Section: P-cresol Clearance In a Simulated Colonic Environmentmentioning
confidence: 99%
“…Though it was initially thought that health benefits were attained by somehow balancing the intestinal microbiota, Stuivenberg et al [27] challenged this notion by showing that the four bifidobacterial strains used in this study sequester p-cresol from their environment. We built on those findings by showing that B. breve HRVD521-US, B. animalis HRVD524-US, and B. longum SD-BB536-JP can clear p-cresol from a mock colonic environment [27,56,57]. The initial study investigating these four strains assessed toxin clearance in media with reduced nutritional content to promote the use of p-cresol as a carbon source [27].…”
Section: Yogurt Supplemented With Probiotic Bifidobacteria Reduce P-c...mentioning
confidence: 99%
“…Yet, the presence of O. formigenes is notably reduced in urolithiasis sufferers, 4,5 , and recent evidence suggests that supplementing with O. formigenes may not effectively lower urinary oxalate levels or prevent stone formation, posing a challenge to existing theories. 6,7 . Additionally, a phase III clinical trial focusing on children with primary hyperoxaluria found no signi cant change in plasma oxalate levels after a year-long treatment with O. formigenes, further questioning the e cacy of such interventions 8 .…”
Section: Introductionmentioning
confidence: 99%